Pemberdayaan masyarakat melalui pelatihan pembuatan ecobrick sebagai upaya mengurangi sampah plastik di Kecamatan Bunga Raya - Muhammad Fauzi; Eni Sumiarsih; Adriman Adriman; Rusliadi Rusliadi; Ika Fitria Hasibuan (Riau Journal of Empowerment, 2020)
Plastics are the synthesis of polymerization of different types of monomers. Almost all kinds of plastic will drift or float inside the water body. It will cause the plastic to be torn apart and damaged by the sunlight, oxidation and abrasion of mechanically forming plastic particles. Ecobrick is one way of handling plastic waste by packing clean and dry plastic into plastic bottles. Community empowerment to process plastic waste into something useful in the long term is one of the keys to the success of the plastic waste recycling program. This activity will provide benefits for community service participants, members who implement counselling, higher education and government. The target audience in these community service activities is the village community Bunga Raya, Siak regency. Results of public service activities that have been implemented by the community have been able to make seats from Ecobrick. In society, it is expected not only to make seats from Ecobrick but also to create other creations. So it can be used as a new business opportunity for the target community.